Endophytic Fungi: A Natural Source of Bioactive Compounds and Biotechnological Applications - Coertjens, Nicole Carneiro; Mascarenhas, Maria do Socorro; Batiatote, Margareth (Fronteiras : Journal of Social, Technological and Environmental Science (Anápolis), 2023)
Endophytic fungi are microorganisms that live inside plants and are a promising source of bioactive molecules. These fungi have aroused a growing interest in research due to their ability to produce a variety of substances. Thus, this study aims to emphasize the relevance of endophytic fungi present in plants as a source of bioactive compounds, which have several applications in biotechnology. For this, scientometrics was used as a methodology, based on a search in the ScienceDirect database using the terms "endophytic fungi", "plants", "metabolites" and "biotechnological application" in a time frame between 2015 and 2022. These fungi have aroused a growing interest in research due to their ability to produce a variety of bioactive compounds. The interaction between endophytic fungi and plants is crucial for plant survival, and many of the compounds produced by fungi have biotechnological potential. Scientometrics revealed an increase in the number of publications on the subject, with emphasis on research studies and reviews. The prospection of endophytic fungi has focused on families of plants with medicinal attributes. These complex interactions between fungi and plants play an important role in plant health and development. Research in this area continues to grow, with many compounds identified as potential bioactive products in diverse biotechnological applications.